PROFESSIONAL JUDGMENT: FENOMENA DI BALIK PENERAPAN IFRS DALAM ASET TETAP PADA LAPORAN KEUANGAN: Studi Fenomenologi Pada Auditor KAP di Semarang dan Jakarta - Arifah, Khilda Faoziyah (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
International Financial Reporting Standards are standards focusedin fair value approach on measurement and disclosure criteria that requirethe greater extent of the exerciseof professional judgment. This study aims tounderstand the exercise of auditor professional judgment in InternationalFinancial Reporting Standards (IFRS) in fair value of fixed assets, tounderstand the factors that contribution in exercising professional judgmenton fair value of fixed assets and what constrains that emerge whenexercising professional judgment in fair value of fixed assets as well assolution that can be done to overcome these problem.This study uses qualitative research methods with aphenomenological approach as it is meant to analyze and look for themeaning behind the experiences of the auditor in exercising their professionaljudgment. This study focused on the exercise of professional judgment on thefair value of fixed assets. The research was conducted through interviewswith auditors who work as public accountants in public accounting firm.Results of this study indicate that auditors exercise their professionaljudgment to review the appraisal value by assessing the reasonableness of theassumptions, methods and data used. Auditors exercise their professionaljudgment by considering the factors that influenced such as consideration ofmateriality, subjectivity, knowledge, and experience as well as factors such asthe audit job IFRS requirements, the nature of accounts, compliances withIFRS, audit history, engagement management, fraud risk and going concern.The auditor had no difficulties in using professional judgment in assessingthe fair value of fixed assets due to the existing appraisal valuation. Insteadauditor experienced problems when assessing the fair value of financialinstruments is important for future research. Finally, team work anddiscussion are solution that auditors used to overcome the problem inexercising professional judgment.